2015
DOI: 10.1016/j.aller.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Many respiratory viruses have temporal association with meningococcal disease

Abstract: The rate of MNG in Chile is temporally associated to all of the respiratory viruses studied, but with variability according age range, and regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…It causes lysis of epithelial cells and other local immunologic damages, enhancing the invasiveness of pathogenic bacteria such as N. meningitidis. RSV has been shown not to affect or influence IMD, and other respiratory viruses have not consistently proven to enhance the invasiveness of N. meningitidis [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It causes lysis of epithelial cells and other local immunologic damages, enhancing the invasiveness of pathogenic bacteria such as N. meningitidis. RSV has been shown not to affect or influence IMD, and other respiratory viruses have not consistently proven to enhance the invasiveness of N. meningitidis [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 98%
“…Influenza infection has been previously associated with IMD, even triggering the latter [11,12]. However, other respiratory viruses, such as respiratory syncytial virus (RSV) and adenovirus, have either not or only suggestively been associated with IMD [13][14][15]. There is only one published case from Scotland of a young adult IMD patient co-infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), resulting in a good outcome [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by J. A. Castro-Rodriguez et al in Chile [3] showed that many respiratory viruses like Respiratory syncytial virus, Influenza virus, Para influenza virus and adenovirus have temporal association with meningococcal disease. The case discussed here also gives a clinical history similar to flu like symptoms following which he developed severe respiratory infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in symptomatic children have identified interferences between upper respiratory tract (URT) viruses and/or bacteria. 8,9,25,26 However, since these studies were performed in symptomatic populations they most likely represent interactions between true pathogens and not merely microorganisms in a carrier stage. The mechanisms underlying viral coexistence in case of asymptomatic patients are probably quite different, given the absence of activated inflammatory pathways, and so the results from the above studies should not be considered directly comparable to our own.…”
Section: Discussionmentioning
confidence: 99%